Essential demographic methods - Wachter, Kenneth W. (Harvard University Press, 2014)
"Classroom-tested over many years and filled with fresh examples, Essential Demographic Methods is tailored to beginners, advanced students, and researchers. Award-winning teacher and eminent demographer Kenneth Wachter draws on themes from the individual lifecourse, history, and global change to bring out the wider appeal of demography" -- Provided by publisher.